Symptomatic Retrocaval Ureter: Case Report - Ardıçoğlu, Arslan; Yüzgeç, Veysel; Semerciöz, Atilla; Bodakçı, M. Nuri; Kanbay, Mustafa (Fırat University, 2002)
The retrocaval ureter is a rare congenital anomaly in which the right ureter passes behind the vena cava inferior, leading to varying degrees of ureteral compression. Its incidence is 1/1500. It has been accepted that an embryological abnormal development of inferior vena cava has a role, on its etiology. In this case report the clinical diagnosis and treatment of symtomatic retrocaval ureter was assessed in a 28 years old male patient.

Retrokaval üreter, sağ üreterin vena kava inferiorun arkasından geçtiği ve değişik derecede üreteral basının oluştuğu, ender konjenital bir anomalidir. Görülme sıklığı 1/1500 oranındadır. Etyolojide inferior vena kavanın gelişimsel anomalisinin rol oynadığı bildirilmiştir. Bu olgu sunumunda, 28 yaşında erkek hastada, semptomatik retrokaval üreterin, klinik teşhis ve tedavisi tartışıldı.
Semptomatik Retrokaval Üreter: Olgu Sunumu